Restructuring of Murabahah Agreement Financing: Case Study at PT Bank Muamalat Banjarmasin Branch Office - Rahmawati, Nisa; Wafa, Faqih El; Gafur, Abdul; Faridah, Faridah; Fitriani, Ahda (AL-SULTHANIYAH, 2025)
This research discusses the problematic financing settlement policy regulated by Peraturan Bank Indonesia (PBI) No. 10/18/PBI/2008, Peraturan Otoritas Jasa Keuangan (POJK) No. POJK.03/2019, and Fatwa Dewan Syariah Nasional-Majelis Ulama Indonesia (DSN-MUI) No. 47, 48, 49/DSN/MUI/II/2005. Furthermore, this study analyses the implementation of these policies at Bank Muamalat KC Banjarmasin concerning relevant regulations. This research uses a qualitative approach through field research methodology, with data collection conducted through direct interviews with relevant informants. After collecting the data, the author describes, describes, and analyses the policy and implementation of financing restructuring with murabahah contracts at Bank Muamalat KC Banjarmasin. The results showed that the murabaha contract financing restructuring policy at the bank has been implemented comprehensively and by the provisions contained in PBI No. 10/18/PBI/2008, POJK No. 10/POJK.03/Year 2019, and DSN-MUI Fatwa No. 47, 48, 49/DSN/MUI/II/2005, which includes three main elements: rescheduling, reconditioning, and restructuring (3R).